The Vasorelaxant and Neuroprotective Effects of Mildronate in A Rabbit Subarachnoid Hemorrhage Model - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2020)
AIM: To investigate the effects of an anti-ischemic agent, mildronate, on subarachnoid hemorrhage-induced vasospasm. MATERIAL and METHODS: Rabbits were randomly divided into four groups: control, subarachnoid hemorrhage (SAH), vehicle, and mildronate (n=8 animals per group). In the treatment group, 200 mg/kg of mildronate were intraperitoneally administered 5 minutes after the procedure and continued for 3 days as daily administrations of the same dose. At the end of the third day, the cerebrum, cerebellum, and brain stem were perfused, fixated, and removed for histopathological examination. Tissues were examined for arterial wall thickness, luminal area, and hippocampal neuronal degeneration. RESULTS: Mildronate group showed significantly increased luminal area and reduced wall thickness of the basilar artery compared with the subarachnoid hemorrhage group. In addition, the hippocampal cell degeneration score was significantly lower in the mildronate group than in the SAH and vehicle groups. CONCLUSION: These results show that mildronate exerts protective effects against SAH-induced vasospasm and secondary neural injury.
Keywords: Anti-ischemic; Mildronate; Neuroprotection; Rabbit; Subarachnoid hemorrhage; GAMMA-BUTYROBETAINE; CEREBRAL VASOSPASM; DOUBLE-BLIND; ORAL NIMODIPINE; INHIBITOR; ERYTHROPOIETIN; THERAPY; ARTERY